Endoscopic sleeve gastroplasty for treatment of class 1 and 2 obesity (MERIT): a prospective, multicentre, randomised trial. Issue 10350 (6th August 2022) - Abu Dayyeh, Barham K; Bazerbachi, Fateh; Vargas, Eric J; Sharaiha, Reem Z; Thompson, Christopher C; Thaemert, Bradley C; Teixeira, Andre F; Chapman, Christopher G; Kumbhari, Vivek; Ujiki, Michael B; Ahrens, Jeanette; Day, Courtney; et al.
Summary: Background: Endoscopic sleeve gastroplasty (ESG) is an endolumenal, organ-sparing therapy for obesity, with wide global adoption. We aimed to explore the efficacy and safety of ESG with lifestyle modifications compared with lifestyle modifications alone. Methods: We conducted a randomised clinical trial at nine US centres, enrolling individuals aged 21–65 years with class 1 or class 2 obesity and who agreed to comply with lifelong dietary restrictions. Participants were randomly assigned (1:1·5; with stratified permuted blocks) to ESG with lifestyle modifications (ESG group) or lifestyle modifications alone (control group), with potential retightening or crossover to ESG, respectively, at 52 weeks. Lifestyle modifications included a low-calorie diet and physical activity. Participants in the primary ESG group were followed up for 104 weeks. The primary endpoint at 52 weeks was the percentage of excess weight loss (EWL), with excess weight being that over the ideal weight for a BMI of 25 kg/m 2 . Secondary endpoints included change in metabolic comorbidities between the groups. We used multiple imputed intention-to-treat analyses with mixed-effects models. Our analyses were done on a per-protocol basis and a modified intention-to-treat basis. The safety population was defined as all participants who underwent ESG (both primary and crossover ESG) up to 52 weeks. Findings: Between Dec 20, 2017, and June 14, 2019, 209 participants were randomly assigned to ESG (n=85) or to control (n=124). At 52 weeks, the primary endpoint of mean percentage of EWL was 49·2% (SD 32·0) for the ESG group and 3·2% (18·6) for the control group (p<0·0001). Mean percentage of total bodyweight loss was 13·6% (8·0) for the ESG group and 0·8% (5·0) for the control group (p<0·0001), and 59 (77%) of 77 participants in the ESG group reached 25% or more of EWL at 52 weeks compared with 13 (12%) of 110 in the control group (p<0·0001). At 52 weeks, 41 (80%) of 51 participants in the ESG group had an improvement in one or more metabolic comorbidities, whereas six (12%) worsened, compared with the control group in which 28 (45%) of 62 participants had similar improvement, whereas 31 (50%) worsened. At 104 weeks, 41 (68%) of 60 participants in the ESG group maintained 25% or more of EWL. ESG-related serious adverse events occurred in three (2%) of 131 participants, without mortality or need for intensive care or surgery. Interpretation: ESG is a safe intervention that resulted in significant weight loss, maintained at 104 weeks, with important improvements in metabolic comorbidities. ESG should be considered as a synergistic weight loss intervention for patients with class 1 or class 2 obesity. This trial is registered with ClinicalTrials.gov, NCT03406975 . Funding: Apollo Endosurgery, Mayo Clinic.